Relating through instructing: affiliative interactional resources used by the teacher when giving feedback on student work. Issue 3 (3rd July 2021) - Shvidko, Elena
ABSTRACT: Providing feedback on student work is a vital part of pedagogy. However, instructors may inadvertently create a distance between themselves and students by asserting authority when evaluating students' work. This may conflict with maintaining a positive atmosphere in the classroom and developing interpersonal solidarity with students, which is crucial for teacher–student rapport. Therefore, it is important for teachers to know how to provide feedback in more affiliative, less threatening ways. Employing multimodal microanalysis of teacher–student interaction, this study demonstrates how one writing teacher used affiliative interactional resources–expressing empathy, being playful, and offering a compliment–in a way that was likely to minimise her imposition, reduce the authoritarian character of her feedback, and create affiliative moments with students while providing feedback on their work. Reflecting on the results of this analysis, the article offers pedagogical implications.